2019
DOI: 10.1051/matecconf/201928005016
|View full text |Cite
|
Sign up to set email alerts
|

Towards sustainable communities: Socioeconomic determinants of domestic water consumption in Surakarta City, Indonesia

Abstract: The gap in water consumption among urban households remains obvious in most cities in Indonesia. It is particularly the case for high-density urban areas. Dense urban areas and limited availability of water resource position water as a contested resource. Regarding water as a contested resource, this paper aims to identify the socioeconomic determinants influencing levels of water consumption in the urbanized medium-sized city, using the case of Surakarta City. Data were collected by using proportional random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Also, the significance of climate and weather variables has been observed to have a significant impact on daily water use in tropical homes (Some researchers have mentioned that more water is used for varying domestic purposes during the daytime, attributed to the high diurnal temperature and usually single-digit daily temperature range in tropical environments ( Slavikova et al 2013, Paramita and Rini, 2019, Bergel and Młyńska 2021. Further supporting this viewpoint, Bergel and Młyńska (2021) and Dimkić (2020) revealed that more water is utilized for drinking when the weather is hot than when it is cold.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the significance of climate and weather variables has been observed to have a significant impact on daily water use in tropical homes (Some researchers have mentioned that more water is used for varying domestic purposes during the daytime, attributed to the high diurnal temperature and usually single-digit daily temperature range in tropical environments ( Slavikova et al 2013, Paramita and Rini, 2019, Bergel and Młyńska 2021. Further supporting this viewpoint, Bergel and Młyńska (2021) and Dimkić (2020) revealed that more water is utilized for drinking when the weather is hot than when it is cold.…”
Section: Introductionmentioning
confidence: 99%